PENGAWASAN PERIZINAN TANDA DAFTAR GUDANG (TDG) PERGUDANGAN KOTA PEKANBARU TAHUN 2014-2016 - Rio Chandra; Erma M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is based on the decisions issued by the Indonesian republic's trade ministry who want the arrangement of the warehouse list sign permit. The purpose of this research is to analyze about how the supervision done by municipal government Pekanbaru as executor of regional autonomy in this case executed by service in charge of commerce.This research is descriptive. This study aims to describe how the real situation in the field accurately and systematically related to research and fact analysis, as well as field observation and data or information obtained. Methods of data collection is done by way of interviews and documentation.The results showed that the policy issued by the minister of commerce of the Republic of Indonesia which became the guideline for the new city government to supervise the warehousing can not be done because there is no regulation peaksana of law number 23 year 2014 about the local government in which regulate the division of authority between the government region / city and province. This is seen from some data provided by the capital investment and integrated services one door kota Pekanbaru which the data since the year of the enactment of policies and regulations regarding the obligation to have the warehouse list licensing list is only 287 warehouses who have the license list warehouse list of 372 warehouse who has been taking care of HO interference permissions. Thus the results of this study indicate that from the data that has been described in this study that the number of warehouses that have permission HO disturbance is not directly proportional to who has a warehouse sign permit.Keywords ; Supervision, Policy, Warehouse, Warehouse Registry, and HO.